8th Conference of the European Ornithologists` Union 27-30 August 2011, Riga - Stępniewska, Katarzyna; Stępniewski, Krzysztof (Zielona Góra: University of Zielona Góra, Faculty of Biological Sciences)
The Conference was organised by the University of Latvia in Riga - the largest university in the country and the host of the Conference - together with the University of Daugavpils and the Latvian Ornithological Society (LOB). About five hundred ornithologists took part in the conference; they represented most of European countries, but there were also several people from Africa and North America.
Keywords: wróblowe; ornitologia